LEGAL UNCERTAINTY IN DIGITAL APPLICATION-BASED TRANSPORTATION SERVICES - Putra, M. Adi; Sara, Rineka (Ridwan Institute, 2024)
The rise of app-based transportation services has led to a shift in lifestyle from conventional to online, from shopping needs to public transportation orders and various other services. The study aimed to explore the legal uncertainty that currently exists in the regulation of apps-based transport services, as well as the barriers and efforts to create legal certainty in this context. This study analyzed the data through a qualitative approach, employing a combination of legal analysis and comparative methods. The results show that the lack of clear regulations regarding the use of two-wheeled vehicles as public transport creates significant weaknesses within the industry. The lack of fair competition principles in Indonesia is an important concern in the context of transportation regulation. This work provides valuable insights for policymakers, regulators, and stakeholders involved in the transportation sector, suggesting pathways for improving regulatory clarity and effectiveness. By analyzing these areas, future research could contribute valuable insights to aid policymakers in creating a more coherent, effective, and responsive regulatory environment that supports the sustainable growth of the app based transportation sector while ensuring the safety and protection of all parties involved. This research could include comparative analyses of successful regulatory models from other jurisdictions that have effectively harmonized their regulations while fostering innovation and consumer protection.